ANALYSIS OF FACTORS AFFECTING THE SUCCESS OF MICRO SMALL AND MEDIUM ENTERPRISES (CASE STUDY OF NAGOYA SHOP IN LHOKSEUMAWE CITY) - Rusydi Abubakar; Rizka Imelia Salsabila; Siti Nurhaliza; Khaira Ummaya; Anisa Br Pelawi (RADJA PUBLIKA, 2023)
This research aims to analyze the profits of the